The potential of wheat germs as a coagulant to treat batik wastewater / Nurhaslina C.R, Ku Halim Ku Hamid and Siti Zuraida Mohamad - C.R, Nurhaslina; Ku Hamid, Ku Halim; Mohamad, Siti Zuraida (Universiti Teknologi MARA, Perlis, 2011)
The purpose of this study is to identify the potential of wheat germs as a coagulant to treat batik wastewater. Dyestuffs present in textile industry wastewater are hardly to degrade by biological means and many synthetic dyes are toxic, mutagenic and carcinogenic. Dye can be removed from wastewater by chemical and physical methods such as adsorption, coagulation and flocculation, oxidation, filtration and electrochemical methods. However, coagulation is one of the most common processes in the water and wastewater treatment. An organic polymer Polyaluminium Chloride (PAC) and inorganic salt Aluminium Sulphate (Alum) are the most widely used coagulant in water treatment. In order to reduces the harmful of chemical coagulants toward environment, the naturally sources coagulants that are easily available and abundantly left without significant usage has been investigated and discovered. For this study, wheat germs will use as the natural coagulant. The newly invented plant based coagulant, wheat germs are the abundantly available agricultural in Malaysia and cheap. Besides that, wheat is categorized in cereal group which is well known as the food that has the ability to absorb cholesterol in blood. Jar Test method was used to conduct the coagulation process for dye wastewater from textiles industries. It is discovered that the wheat germ has successfully removed 66% of COD, 87% of turbidity and 86.5% of color of the dye wastewater through coagulation process. Based on this fact, wheat germs have a big potential to become as anatural coagulant to treat textiles wastewater.